Problematization of phylosophy teaching and teacher formation in Brazil - Avanço, Leonardo Dias [UNESP] (FapUNIFESP (SciELO), 2020)
Problematization of Phylosophy Teaching and Teacher Formation in Brazil. The objective of this study is to enlighten two problems: the first regards the obstacles that oppose acknowledging the broadening of the concept of Philosophy, whereas the second concerns resuming the comprehension of the specific nature of philosophical activity. The con-cepts of humanity and philosophy are approached in a uni-versal perspec-tive, as well as the original anthropological function of teaching. The study aims to contribute with enhancing the freedom of educative intervention by philosophy teachers in Brazil. The conclusion proposes an expansion of the concept of philosophy and encourages teaching practices that set the conditions for a harmonious and multi-rational coexistence among various forms of love for wisdom.
Problematização do ensino e da formação de professores de filosofia no Brasil atual
Keywords: Diversity; Education; Teaching; Unity; Universality